TikTok Influencers and the FoMO Phenomenon: Exploring Tourist Behavior at Popular Destinations - Sarah Sasmita; Yusri Abdillah; Fahrudi, Agung Nugroho Luthfi Imam (Wacana Journal of Social and Humanity Studies, 2026)
This article presents the results of a study that analyzes the influence of TikTok influencers on the Fear of Missing Out (FoMO) phenomenon on the decision to visit Jawa Timur Park 3. The research examines influencer attributes such as attractiveness, expertise, and similarity, which affect consumer trust and FoMO, ultimately driving visit decisions. The study employs an explanatory research method with a quantitative descriptive approach, involving 280 respondents who had visited Jawa Timur Park 3 after being exposed to TikTok content. Data collection was conducted through an online questionnaire and analyzed using Structural Equation Modeling (SEM-PLS). The results indicate that TikTok influencers have a substantial impact on FoMO, primarily through their credibility, which fosters audience trust and engagement. The study highlights the importance of selecting credible influencers to create authentic, visually appealing, and audience-relevant content. These findings contribute to the understanding of psychological mechanisms in social media marketing within the digital tourism industry, underscoring the importance of trust-based marketing strategies in enhancing visitor experiences.   Keywords: TikTok influencers, Fear of Missing Out (FoMO), digital tourism, consumer trust.